2004
DOI: 10.1183/09031936.04.00076704
|View full text |Cite
|
Sign up to set email alerts
|

A population-based study of the costs of care for community-acquired pneumonia

Abstract: A population-based study of the costs of care for community-acquired pneumonia. M. Bartolomé, J. Almirall, J. Morera, G. Pera, V. Ortún, J. Bassa, I. Bolíbar, X. Balanzó, A. Verdaguer, and the Maresme Community-Acquired Pneumonia Study Group (GEMPAC). #ERS Journals Ltd 2004. ABSTRACT: In a population-based study, the consumption of resources for treating adult patients with community-acquired pneumonia was determined.During a 2-yr period, all cases with a clinical and radiological suspicion of community-acquir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
60
4
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 33 publications
5
60
4
6
Order By: Relevance
“…In the present study, the documented costs were slightly higher than those reported in the national and European literature. In other studies carried out in Spain, the direct costs of in-patient care were J1,210 [8] and J1,553 [7]. In Europe, the direct costs ranged from J1,333…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the documented costs were slightly higher than those reported in the national and European literature. In other studies carried out in Spain, the direct costs of in-patient care were J1,210 [8] and J1,553 [7]. In Europe, the direct costs ranged from J1,333…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a number of publications have analysed the economic aspects of CAP, aiming to evaluate costs in outpatients and in those admitted to the hospital or intensive care unit (ICU) [7,8]. BAUER et al [4] also found that direct costs correlated with initial severity as measured by the Pneumonia Severity Index (PSI) [9].…”
mentioning
confidence: 99%
“…3 But in other study it was found importantly higher expense in patients 65 years of age, but no details were provided on the effect of comorbidity and severity. 11 In the present study it was found that the patient with no comorbidity consumed less cost as compare to the patients with the comorbidity and the cost was found much higher in patient with the comorbidity of cardiovascular disease. Comparing to other study it was determined that co-morbid diseases increased the total cost, but at higher ages (> 65 year) there was no effect on the total cost 4 but in 2001 in another study it was; described that age and co-morbid disease had no effect on the total cost of CAP.…”
mentioning
confidence: 53%
“…El ingreso mensual promedio de IC95%, 2,1-2,8) en casos de neumonías presuntamente bacterianas, con un costo medio de US$ 36,80 (IC95%, 19,5-54,2). Dentro del grupo de "otros" medicamentos administrados se encuentran los líquidos endovenosos, los broncodilatadores, antiemé-ticos, antiulcerosos, vitaminas y protectores cutáneos, entre otros, con un número promedio de administración de 3,8 (IC95%, 3,1-4,6) y un costo de US$ 12,14 (IC95%, 7,[8][9][10][11][12][13][14][15][16]5).…”
Section: Resultsunclassified
“…En la literatura latinoamericana son escasos los estudios económicos que valoren los costos de las neumonías en la población infantil, por lo que puede servir de punto de referencia respecto a América Latina. Los estudios que valoran los costos de las neumonías en países desarrollados se refieren prioritariamente a neumonías en el adulto mayor (12)(13)(14)(15).…”
Section: Discussionunclassified